2018
DOI: 10.1080/09553002.2018.1440094
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced G2/M arrest rarely occurred in glioblastoma stem-like cells

Abstract: We explored the cell-cycle alterations and cell-cycle-related proteins expression levels in GSLCs after irradiation, providing a novel mechanism of radioresistance of GSLCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
3
13
1
Order By: Relevance
“…We used two markers of apoptosis, cleaved-Parp and cleaved-Caspase 3, to evaluate apoptotic response after irradiation in the three GSC populations. We observed a dose-dependent increase in both cleaved-Parp and cleaved-Caspase 3 ( Fig 5D ) in GSCs, consistent with the literature [ 21 ]. There were no apparent differences in the expression levels of cleaved-Parp or cleaved-Caspase 3 between the two dose rates.…”
Section: Resultssupporting
confidence: 91%
“…We used two markers of apoptosis, cleaved-Parp and cleaved-Caspase 3, to evaluate apoptotic response after irradiation in the three GSC populations. We observed a dose-dependent increase in both cleaved-Parp and cleaved-Caspase 3 ( Fig 5D ) in GSCs, consistent with the literature [ 21 ]. There were no apparent differences in the expression levels of cleaved-Parp or cleaved-Caspase 3 between the two dose rates.…”
Section: Resultssupporting
confidence: 91%
“…13,14,31,32 However, a portion of patients suffer from resistance to radiotherapy, which characterized by continuous proliferation and tumor relapse after standard radiotherapy. 20,33 Although there has been a wealth of studies that attempt to unveil the underlying mechanisms of radioresistance, none of them can fully accommodate the issues faced by oncologist possibly due to lack of in-depth understanding of radioresistance. In the present study, we focused on radio-response of the cells from NPC, to which radiotherapy has been a first-line treatment in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The protein phosphatase Cdc25C regulates entry into mitosis by activating the Cdc2/CyclinB1 kinase complex. At the onset of mitosis, Cdc2 is dephosphorylated by Cdc25C at Threonine‐14 (Thr‐14) and Tyrosine‐15 (Tyr‐15), the Cdc2/CyclinB complex translocates into the nucleus, and the cell cycle progresses into M phase . Cdc25C and Cdc2 are both critical regulators in G2/M transition and are modulated by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Tyrosine-15 (Tyr-15), the Cdc2/CyclinB complex translocates into the nucleus, and the cell cycle progresses into M phase. 32 Cdc25C and Cdc2 are both critical regulators in G2/M transition and are modulated by many factors. Some studies have suggested that activation of the ATM/Chk1 pathway could inhibit Cdc25C activation, thereby preventing dephosphorylation of Cdc2 and entry into mitosis, as well as cell cycle arrest at the G2/M phase.…”
Section: Effect Of Ost On Er Stress Associated Protein Expression Imentioning
confidence: 99%